Reducing of energetic costs for drying process for candied pears production - Atamanyuk, Volodymyr; Huzova, Iryna; Patrii, Nataliia (Lviv Polytechnic Publishing House, 2016)
According to calculations of the heat balance were calculated amounts of energy accumulated by pears layer and energy required to evaporate moisture. It was determined that reduce of energy costs for candied fruits drying is achieved by final drying at ambient temperature.
Keywords: candied pear; drying; temperature conditions; kinetics; heat balance